Creation of an information and logistics service center as a factor of increasing logistic service - Yergaliyev, R.; Raimbekov , Zh. (BUKETOV BUSINESS REVIEW, 2017)
The article deals with the issues of creatingthe center for information and logistic service and its role in enhancing logistics services. The Center for Information and Logistic Services will function on the principle of a «single window» and cover the entire logistic chain, uniting the subjects of the logistic process - both state bodies and private companies - into a single information space. Logistics organization through the center for information and logistics service will include a wide range of services of a larger number of logistics companies with the possibility of using their combined assets: cargo yards, warehouses, sites, rolling stock, car fleet, equipment and technologies. In addition, it is known from the experience of developed countries that when using information and logistics systems by enterprises, their transportation costs are reduced by 7-20 %, the costs of handling and storage of material resources are reduced by 15-30 %, and the total logistics Costs by 12-35%. The authors come to the conclusion that the new format of interaction «customer-carrier» on the basis of information-logistic service will allow all participants to reduce response time, reduce staff costs, ensure transparency and flexibility of tariffs and eliminate the risk of errors in communications.